2016
DOI: 10.2131/fts.3.101
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex expression in a rotenone model of Parkinson’s disease in rats

Abstract: Animal models can help determine the etiology of neurodegenerative diseases such as Parkinson's disease. Here, we conducted transcriptome analysis of the rotenone model of Parkinson's disease in rats. Exposure of 9-week-old Wistar rats to rotenone at 3 mg/kg/day for 14 days reduced spontaneous motor activity to 49% of that of control rats. Immunohistochemical analysis revealed increased expression of major histocompatibility complex (MHC) molecules in the substantia nigra of rotenonetreated rats, which was ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…As mentioned above, rotenone has been shown to be a dopaminergic toxin, developing Parkinson's disease with adult rats (Betarbet et al, 2000;Ishido and Shimaya, 2016) and we demonstrated that exposure of rat pups to rotenone causes hyperactivity during juvenile and adulthood due to dopaminergic lesions by rotenone (Ishido et al, 2017).…”
Section: Rotenone and Behavioral Phenotypessupporting
confidence: 60%
See 3 more Smart Citations
“…As mentioned above, rotenone has been shown to be a dopaminergic toxin, developing Parkinson's disease with adult rats (Betarbet et al, 2000;Ishido and Shimaya, 2016) and we demonstrated that exposure of rat pups to rotenone causes hyperactivity during juvenile and adulthood due to dopaminergic lesions by rotenone (Ishido et al, 2017).…”
Section: Rotenone and Behavioral Phenotypessupporting
confidence: 60%
“…Thus, spontaneous motor activity of these two kinds of animal models could be quantitative index. We employed Supermex® system to measure spontaneous motor activity, as described previously ( Masuo et al ., 1997( Masuo et al ., , 2007Masuo and Ishido, 2011 ;Ishido et al ., , 2004cIshido et al ., , 2004dIshido et al ., , 2005Ishido et al ., , 2017Ishido and Shimaya, 2016 ). A Supermex® sensor head comprising paired infrared pyroelectric detectors was used to measure the radiated body heat of each animal.…”
Section: Measurements Of Spontaneous Motor Activity For Behavioral Phmentioning
confidence: 99%
See 2 more Smart Citations